Three Iridoid Glycosides from the Root extract of Stachytarpheta angustifolia Mill Vahl Verbenaceae - Mohammed, M.; Bugaje, I. M.; Garba, M. A. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Three iridoid glycosides were isolated from the n-butanol fraction of the root extract of Stachytarpheta angustifolia (verbenaceae). Their structures were elucidated by using a combination of 600MHz/150 MHz ID and 2D NMR techniques (COSY, NOESY, DEPT, HSQC and HMBC) and by FABMS and HRESIM. Compound 1 was characterized as Citrifolinoside, (2) as Serratoside and 3 is determined as 6 – O – (3 " – O – trans – cinnamoyl) - α – L – rhamnopyranosyl catalpol heptaacetate.